Deferred Reference of Proper Names. (8th March 2021) - Kijania-Placek, Katarzyna; Banaś, Paweł
Abstract: In this paper, we argue that proper names have deferred uses. Following Geoffrey Nunberg, we describe the deferred reference mechanism by which a linguistic expression refers to something in the world by exploiting a contextually salient relation between an index and the referent in question. Nunberg offered a thorough analysis of deferred uses of indexicals but claimed that proper names do not permit such uses. We, however, offer a number of examples of uses of proper names which pass grammatical tests for deferred usage, as put forward by Nunberg.